Relationship between social support and mental health of left-behind children among middle school students in Zigong city, China - Yike, Wan; Hassan, Siti Aishah; Zuchang, Bin; Pingping, Gui; Jin, Wei; Lei, Zhou; Zhouyuan, Gao (Human Resource Management Academic Research Society, 2023)
There are over 68 million left-behind children in the rural villages in China, with at least one parent working and staying in the city. Empirical evidences indicated that left-behind children endure many challenges concerning their welfare and education. The present study aims to examine the relationship between social support and mental health among middle school students under the background of left-behind children in Zigong City, China. The correlational research design was adopted in this study. Cluster sampling was used to recruit a sample size of 235 middle school students from Zigong City, China. The results indicated that the left-behind middle school students who reported receiving greater social support were led to report having better mental health. It also provides the suggestions for government, social workers, educators, and caregivers to provide sufficient care and support for the left-behind families.